The Role of Public Speaking Training to Build Self-Confidence For Class One Intensive Students of Darussalam Gontor Islamic Boarding School for Girls - Ahmad Hidayatullah Zarkasyi; Sekar Ayu (Educan : Jurnal Pendidikan Islam, 2018)
There were several terms of new student of  Islamic Boarding School Darussalam Gontor. It might be shocked and unfamiliar with the boarding school, from all kinds of regulations and activities that are felt to be endless. It could be found various  problem that experienced by new student such public speaking. Public speaking or speech presentation training is new activity that they just met. it was considered quite difficult which was filled with kinds of regulations. However, without realizing the existence of Public Speaking, it could build and form good characters accordance with the expectations and ideals of Darussalam Modern Islamic Institution Gontor, especially the character of self-confidence. This research was descriptive. It was analyzed using qualitative methods. To collect the data, the researcher used Interview, Observation, and Documentary. The data technical  used analysis Miles and Huberman those are: Reduction DATA, Display Data and Conclusion Drawing &Verification. The result of this research describe that: (1) Public Speaking in Darussalam Modern Islamic Institution Gontor starts with: preparation in writing speech papers, correcting and justifying papers, corrected and evaluated by close friend when practicing speech, delivering speech in public, cheered on by cheers from the audience, and judges by supervisor of public speaking. (2) Public Speaking can foster and shape the confidence with the practice of speech that is continuous, sequential, repeated. With the great preparation, special speech training for a new students, division of public speaking room, and the support also motivation of various parties.